PSYCHOLINGUISTIC ASPECTS OF BILINGUALISM IN CHILDREN - Sameera J. (International Journal of Literature and Language Studies, 2022)
This paper will consider psycholinguistic aspects of bilingualism from two perspectives: the psychology of the individual and social psychology. After a description of the linguistic development of bilingual children, we present research comparing bilingual and monolingual children with respect to cognitive development. Following that, we will discuss the emotional importance of speaking the parents' language and the reasons for bilingual children's relatively high rates of school failure. The role of attitude and motivation in language maintenance and loss, as well as in the acquisition of a second language, will be discussed in the context of social identity theory. The paper will conclude with suggestions for recommendations.